FLORISTIC CHANGES IN A SUB-TROPICAL RAIN FOREST SUCCESSION - Abdulhadi, Rochadi (REINWARDTIA, 1992)
Floristic changes in a subtropical rain forest were assesed. Three regrowth forests aged 20 years, 50 years and 60 years and an undisturbed forest were sampled. The series of sites sho floristic changes that would be expected in a successional sequence. The regrowth forests were dominated by the secondary species but the primary species occur from the early stage. The oldest regrowth (60 year old-site) was still well short of regaining its original condition.